Implementing precision feeding in Indonesia’s dairy sector: Environmental and socioeconomic impact and adoption challenges - Norma Nuraina; Fauzan Muzakki (Jurnal Inovasi Pangan dan Gizi, 2026)
Background: Lack of proper feeding management leads to low milk quality and quantity in some countries, such as Indonesia. Precision feeding (PF), as one of the precision livestock farming (PLF) practices, is a potential solution to address this problem. This study aims to describe PF applications and their impacts on environmental and socio-economic dimensions, analyze potential challenges in its implementation in Indonesia, and propose solutions to support future PF adoption. Methods: This study was a literature review initiated by searching scientific articles from three databases (ScienceDirect, MDPI, and ResearchGate), resulting in 16 research articles included in the analysis. Finding: There are four main components of PF: nutrient and feed quality adjustment, feed management, technology use, and data-driven model exploration. PF is associated with environmentally friendly practices and can increase farmers’ profitability. PF also introduces a new perspective in dairy farming due to technological interventions. In Indonesia, challenges in applying PF are related to the farming conditions dominated by smallholder farmers and the lack of stable internet connectivity and coverage. The presence of cooperatives can serve as a bridge between PF practices and smallholder farmers. Conclusion: The PF approach can support sustainable dairy farming in Indonesia, contribute to national goals, and address global challenges to meet increasing demand. Novelty/Originality of this article: This study uniquely integrates evidence on precision feeding in dairy farming with its socio-economic impacts, with a focus on Indonesian smallholder systems, linking feeding practices to profitability, sustainability, and farm management across multiple studies.